Energy Efficiency and Battery Load Sharing Analysis of 26-m Electric Supply Boat Using MATLAB - Atikah Rafiah; Surya Hariyanto (Naval Architecture Department, Kalimantan Institut of Technology, 2026)
Load division between parallel battery units in dual-bus battery-electric vessels directly governs current imbalance and battery degradation, yet design-stage quantification remains limited. This study evaluates three battery sharing strategies for a 26-m electric supply boat with a 1,242 kWh LFP system under dual-bus DC architecture across five operating conditions using MATLAB with Coulomb counting and the Rint model. Power demand peaked at 644.31 kW at Transit 12 knots, where propulsion consumed 93.1% of the total energy budget. The optimal strategy achieved 0.0% load imbalance in four of five conditions against a static maximum of 8.2%, reducing the Joule loss index by 0.06% to 485,596 A2. The SOC-adaptive strategy worsened imbalance at Transit 12 knots from 1.5% to 7.8%, confirming that gradient-based shifting is structurally unsuitable for dual-bus battery-only vessels. Terminal voltage analysis identified the DC bus threshold as the binding operational constraint during full-load transit rather than the BMS protection limit, a finding with direct implications for load shedding procedure design in comparable all-electric workboats.